• 2021-04-14
    F[x]中,若f(x)g(x)=2,则f(x^2)g(x^2)=
  • 2.0

    内容

    • 0

      设$f(x)=x^2$,$g(x)=2^x$, 那么 $f \circ f \circ g=$ A: $2^{x^4}$ B: $2^{4x}$ C: $x^{2^{2x}}$ D: $x^{2^{x^2}}$

    • 1

      下列函数相等的是( )。 A: \( f(x) = \ln {x^2},g(x) = 2\ln x \) B: \( f(x) = x,g(x) = \sqrt { { x^2}} \) C: \( f(x) = \sqrt { { x^2}} ,g(x) = \left| x \right| \) D: \( f(x) = { { {x^2} - 1} \over {x - 1}},g(x) = x + 1 \)

    • 2

      下列各选项中,函数相同的是( )。 A: \(<br/>f(x) = \ln {x^2},g(x) = 2\ln x \) B: \(<br/>f(x) = x,g(x) = \sqrt { { x^2}} \) C: \(<br/>f(x) = \sqrt { { x^2}} ,g(x) = \left| x \right| \) D: \(<br/>f(x) = { { {x^2} - 1} \over {x - 1}},g(x) = x + 1 \)

    • 3

      证明:G(x)^2|F(x)^2,当且仅当G(x)|F(x)

    • 4

      下列推导正确的是 。 A: (1) F(x)→G(x) 前提引入 (2)∃xF(x)→G(x) (1)EG B: (1)F(a)→G(x) 前提引入 (2)∃x(F(x)→G(x)) (1)EG C: (1) F(a)→G(x) 前提引入 (2)∃y(F(y)→G(x)) (1)EG D: (1) F(a)→G(x) 前提引入 (2)∃xF(x)→G(x) (1)EG